SPEECH GENRES IN RUSSIAN AND UZBEK LINGUISTICS: THE ART OF COMMUNICATION THROUGH THE WORD (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
The article examines various speech genres and their importance in our daily lives. A person communicates using various forms and styles of speech. From simple everyday conversations to formal speeches, speech genres play an important role in communication. Speech genres are certain forms of speech that express the features of a communicative situation and the corresponding goals of communication.